Volume 4: Manufacturing Materials and Metallurgy; Ceramics; Structures and Dynamics; Controls, Diagnostics and Instrumentation; 1997
DOI: 10.1115/97-gt-531
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Plasma Sprayed and Electron Beam-Physical Vapor Deposited Thermal Barrier Coatings

Abstract: Laboratory testing was conducted on air plasma sprayed (APS) and electron beam-physical vapor deposited (EB-PVD) thermal barrier coatings (TBCs) applied onto nickel alloy specimens. As-coated chemistry, microstructure, and bond strength of the TBC systems were evaluated. Cyclic oxidation tests that simulated industrial gas turbine environments were also conducted on the various thermal barrier coatings. This study evaluated the effects of ceramic and metallic coating compositions and application processes on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The specimen was oxidized in air at 11218C for successively longer periods of time (1,2,4,8,16, 32 h). After each oxidation the sample was cooled to room temperature and the photostimulated Cr 3+ uorescence (luminescence) spectrum recorded.…”
Section: Residual Stress Evolution On Oxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…The specimen was oxidized in air at 11218C for successively longer periods of time (1,2,4,8,16, 32 h). After each oxidation the sample was cooled to room temperature and the photostimulated Cr 3+ uorescence (luminescence) spectrum recorded.…”
Section: Residual Stress Evolution On Oxidationmentioning
confidence: 99%
“…In this work we present experimental observations suggesting that one failure mode is associated with a compositional change in the thermally grown oxide from alumina to a mixture of chromia and spinel, and that this is, in turn, associated with depletion of Al from the bond-coat and concurrent enrichment of Co, Ni and Cr in the oxide. Failure of alumina scales on overlay oxidation coatings has previously been associated with aluminum depletion e ects [1±3] and it has recently been implicated in the failure of TBCs on a MCrAlY bond-coat [4].…”
Section: Introductionmentioning
confidence: 99%
“…1). Intrusive oxidation was reported for different MCrAlY projected coatings, with a sensitivity not clearly associated to a deposition process [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. For instance, several authors reported that HVOF MCrAlY coatings were less prone to intrusive oxidation compared to APS (or even low pressure plasma spraying (LPPS)) [20,23,25].…”
Section: Origin Of Intrusive Oxidationmentioning
confidence: 99%
“…However, these projected coatings are much more prone to internal defects such as unmelted particles, pores, internal oxides and/or nitrides, intersplats. Oxygen ingress along these open channels causes oxide intrusions within the coating [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. This oxide intrusion, concomitant to external oxide scale growth, participates in the Al consumption.…”
Section: Introductionmentioning
confidence: 99%
“…There is a tremendous amount of experience using IBCs in aerospace engines (Marithcchi, etal., 1995;Bose and DeMasi, 1995). Unfortunately, there is limited TBC experience in industrial gas turbine environments (Mutasim, eta, 1997;Nelson and Orenstein, 1995), which show substantially different conditions. Industrial gas turbines (1GT) operate for substantially longer cycles and times between overhauls, and thus endurance becomes a critical factor.…”
Section: Introductionmentioning
confidence: 99%